Size Enlargement of CsPbI3 Perovskite Nanocrystals by Trioctylphosphine in the Synthesis for Highly Efficient Deep‐Red Light‐Emitting Diodes - Huiyuan Cheng; Yifan Zheng; Yu Lou; Mengjie Sun; Guodong Zhang; Haoran Wang; Tom Wu; Yang Bai; Yuchuan Shao (Advanced Electronic Materials)
Abstract Metal halide perovskite nanocrystals (PNCs) hold great promise for light‐emitting diodes (LEDs) due to their high photoluminescence quantum yields (PLQY), tunable colors, and low‐cost solution processability. However, their electroluminescence efficiencies are currently limited by the small size of the PNCs and the weak binding between ligands and PNCs. The small size makes PNCs sensitive to environmental factors due to their large specific surface area, leading to a loss of PLQY during post‐treatment. Additionally, the weak binding between ligands and PNCs causes the ligands to detach during post‐treatment, further reducing PLQY. To address these challenges, an in situ ligand‐capped synthesis method is introduced for PNCs, replacing the aliphatic solvent octadecene (ODE) with trioctylphosphine (TOP). The presence of TOP increases the concentration of monomers, accelerating nucleation and crystal growth, enabling the production of cubic PNCs ranging from 8 nm to over 28 nm. Moreover, TOP acts as a ligand to resurface PNCs, enhancing their stability and maintaining high PLQY after post‐treatment. As a result, by utilizing these larger PNCs, a high maximum external quantum efficiency (EQE) of 21.23% in LEDs is achieved. This method provides a significant advancement in the development of high‐performance PNC‐based LEDs.